Developing analytical skills through optimizing the learning process by science teachers in Nganjuk Regency - Yakub, Pramita; Puspitawati , Rinie Pratiwi; Bashri, Ahmad (Journal of Community Service and Empowerment, 2021)
Based on the results of the interviews, it was found that science teachers in Nganjuk Regency did not understand and master the skills of analyzing, especially with Biology material so that there was a need for training to practice analytical skills through optimizing learning. This training activity aimed to develop analytical skills through optimizing the learning process. This training activity involved 10 junior high school teachers who are members of Â the Science Subject Teacher Association (Musyawarah Guru Mata Pelajaran/MGMP) of Nganjuk Â Regency. The method used was observation and data were analyzed in descriptive qualitative. The implementation of the activities were divided into three stages, namely the preparation, implementation, and evaluation stages and feedback, as well as participant responses. The results of the responses based on the questionnaire were positive with a score of 3.82, very good training material at 3.82, and very good training conditions with a score of 3.84. There was an increase in the learning analysis skills of MGMP participants with a percentage of 82.40%.